2012
DOI: 10.1007/s13225-012-0207-4
|View full text |Cite
|
Sign up to set email alerts
|

Towards a natural classification of Botryosphaeriales

Abstract: Spencermartinsia and Vestergrenia were examined and fresh specimens of Botryosphaeriales were collected from Thailand. This material is used to provide a systematic treatment of Botryosphaeriales based on morphology and phylogeny. Two new genera, Botryobambusa and Cophinforma are introduced and compared with existing genera. Four species new to science, Auerswaldia dothiorella, A. lignicola, Botryosphaeria fusispora and Phaeobotryosphaeria eucalypti, are also described and justified. We accept 29 genera in Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
196
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(201 citation statements)
references
References 96 publications
0
196
1
4
Order By: Relevance
“…However, a comprehensive comparison between these two species was not possible on account of the unavailability of illustrations and detailed descriptions of A. chlorostroma. The sexual morph of A. thailandica is morphologically similar to Bagnisiella australis, which forms multiloculate ascostromata, short, apically rounded asci and ellipsoid, hyaline ascospores (Liu et al 2012, Thambugala et al 2014). However, they differ in their ascospore characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a comprehensive comparison between these two species was not possible on account of the unavailability of illustrations and detailed descriptions of A. chlorostroma. The sexual morph of A. thailandica is morphologically similar to Bagnisiella australis, which forms multiloculate ascostromata, short, apically rounded asci and ellipsoid, hyaline ascospores (Liu et al 2012, Thambugala et al 2014). However, they differ in their ascospore characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…According to Hyde et al (2011) and Liu et al (2012) Aplosporella is an asexual genus circumscribed by multilocular pycnidial conidiomata embedded in stromatic tissues opening by a communal ostiole. Conidiophores are reduced to hyaline, phialidic conidiogenous cells and conidia are aseptate, ellipsoid to subcylindrical, initially hyaline, thinwalled and smooth, becoming pigmented, thick-walled and spinulose (Sutton 1980).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taxonomic studies have shown that a morphological characterization is insufficient for the clear identification of this species; thus, sequencing methods should be used as an important tool for their identification. Other researchers Abdollahzadeh et al 2013;Liu et al 2012) made a reclassification of these fungi by undertaking other regions of highly conserved ribosomal DNA genes, such as: 5.8s, 28s, and also the β-tubulin gene, so it is recommended to perform a deeper identification study in this strain.…”
Section: Itd-g12mentioning
confidence: 99%
“…To perform Bayesian analysis, the model of evolution was estimated by using MrModeltest 2.2 (Nylander 2004) with the nucleotide substitution models selected for combined datasets as GTR+I+G. Posterior probabilities (PP) (Rannala & Yang 1996) were established by Markov Chain Monte Carlo sampling (MCMC) in MrBayes v 3.0b4 (Liu et al 2012). Six simultaneous Markov chains were run for 1,000,000 generations and trees were sampled every 100 th generations (Cai et al 2006).…”
Section: Phylogenetic Analysesmentioning
confidence: 99%